Ultrathin polyamide nanofiltration membranes with tunable chargeability for multivalent cation removal - Wang, Zhen; You, Xinda; Yang, Chao; Li, Wenwen; Li, Yafei; Li, Ya; Shen, Jianliang; Zhang, Runnan; Su, Yanlei; Jiang, Zhongyi (Journal of membrane science, 2022)
Positively charged nanofiltration membranes are promising in water softening and heavy metal ion removal. However, facile modulation on their chargeability remains a great challenge. Here, we proposed a charged-monomer-engineered interfacial polymerization toward positively charged polyamide membranes. In particular, branched amino macromolecules (BAMs) with different charged group numbers and molecular sizes were selected as aqueous monomers, allowing for wide-range-tunable membrane chargeability. We found that larger BAMs tend to form intramolecularly crosslinked networks with more amino residues, conferring membrane chargeability up to +5.53 mC m−2. Besides, the slower diffusion of larger BAMs also led to ultrathin membranes down to 9.0 nm in thickness. The optimal composite nanofiltration membrane displayed a high rejection to multivalent cations (e.g., MgCl2 rejection of 98.7%) with ultrahigh pure water permeance of 31.5 L m−2 h−1 bar−1, which was around 2–10 times higher than that of the reported positively charged nanofiltration membranes. Our monomer design strategy for interfacial polymerization may evolve into a facile approach to constructing advanced charged membranes. [Display omitted] •Ultrathin positively charged polyamide membranes were made by IP process.•The membrane chargeability was tuned by unreacted amino groups in PEI molecules.•The membrane thickness was reduced by decreasing the diffusion rate of PEI in IP.•The membrane exhibits 31.5 (L m−2 h−1 bar −1) water flux, 98.7% MgCl2 rejection.